Consciousness and inward electromagnetic field interactions - MacIver, M. Bruce (Frontiers in Human Neuroscience, 2022)
Electromagnetic field (EMF) theories of mind/brain integration have been proposed to explain brain function for over seventy years. Interest in this theory continues to this day because it explains mind-brain integration and it offers a simple solution to the “binding problem” of our unified conscious experience. Thus, it addresses at least in part the “hard problem” of consciousness. EMFs are easily measured and many corelates have been noted for field activity; associated with loss and recovery of consciousness, sensory perceptions, and behavior. Unfortunately, the theory was challenged early on by experiments that were thought to have ruled out a role of EMFs in brain activity, and the field of neuroscience has since marginalized EMF theories. Here I explain why early evidence against EMFs contributing to consciousness was misinterpreted and offer an alternative view to help direct future research.